Efektivitas Penggunaan Podcast dalam Pembelajaran Bahasa Kedua di Perguruan Tinggi - Salsabila Lasfitri Putri Primarian; Muhamad Fadly Naufal Gunawan; Rebeka Widi Novianingsih (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2021)
This study aims to explore the effectiveness of using podcasts as an aid in second language learning at the university level. In the rapidly evolving digital era, podcasts have become a popular and easily accessible medium for students. This research employs a quantitative method with a quasi-experimental approach involving 60 students from two groups: an experimental group that uses podcasts as a learning medium and a control group that uses traditional methods. The results indicate that students who used podcasts showed significant improvements in listening and speaking skills compared to the control group. These findings suggest that podcasts can be an effective learning tool to enhance second language proficiency in higher education.